Ultra-Processed Food Consumption during Pregnancy and Its Association with Maternal Oxidative Stress Markers - Ameyalli M. Rodríguez-Cano; Isabel González-Ludlow; Blanca V. Suárez-Rico; Araceli Montoya-Estrada; Omar Piña-Ramírez; Sandra B. Parra-Hernández; Enrique Reyes-Muñoz; Guadalupe Estrada-Gutierrez; Claudia C. Calzada-Mendoza; Otilia Perichart-Perera (MDPI AG, 2022)
Ultra-processed food (UPF) consumption during gestation may lead to increased oxidative stress (OS) and could affect pregnancy outcomes. This study aims to evaluate the association of UPF consumption during pregnancy with circulating levels of OS markers. Diet was assessed (average of three assessments) in 119 pregnant women enrolled in the OBESO perinatal cohort (Mexico), obtaining quantitative data and the percentage of energy that UPFs (NOVA) contributed to the total diet. Sociodemographic, clinical (pregestational body-mass index and gestational weight gain) and lifestyle data were collected. Maternal circulating levels of OS markers (malondialdehyde (MDA), protein carbonylation (PC), and total antioxidant capacity (TAC)) were determined at the third trimester of pregnancy. Adjusted linear regression models were performed to analyze the association between UPFs and OS markers. UPFs represented 27.99% of the total energy intake. Women with a lower UPF consumption (<75 percentile°) presented a higher intake of fiber, ω-3, ω-6, and a lower ω-6/3 ratio. Linear regression models showed that UPFs were inversely associated with TAC and MDA. Fiber intake was associated with PC. UPF intake during pregnancy may result in an increase in oxidative stress. When providing nutrition care, limiting or avoiding UPFs may be an intervention strategy that could promote a better antioxidant capacity in the body.